Down hanging sponge (DHS) for nutrient removal in wastewater treatment - Tan, Jian Yu (2021)
Water pollution has emerged to be a global issue for the past few decades that shows significant impacts to the environment and human health. Nutrients consist of nitrogen and phosphorus are the most common pollutant that contribute to the degradation of water quality. Conventional wastewater treatments such as activated sludge process and trickling filter are costly and unaffordable to the developing countries. Down-flow hanging sponge system (DHS) is proposed to be an innovative solution for the prevalent wastewater treatment problem due to its simplicity and affordable cost. In this study, the nutrients removal efficiency was investigated among the six types of DHS system. Several major factors influencing the performance of DHS system and microbial community in DHS reactor were also investigated. The review report commenced with collecting the published research papers followed by analyzing the data collected and lastly summarizing their findings to produce an overall review. From the findings, it was observed that DHS system exhibited satisfactory nutrients removal as well as excellent organic matter removal. Third generation and sixth generation DHS reactor showed better nutrients removal with more than 70 % ammonium nitrogen removal from most of the past research papers. Next, for the microbial community in DHS reactor, the compositions varied along with the height of the reactor. The bacteria involved in organic removal and nutrients removal was detected. Other functionality bacteria related to methane removal, sulfur removal and sludge degradation were also detected in the reactor. In addition, the performance of DHS reactor could be further enhanced by taking the parameters such as HRT, HLR, OLR, operating temperature, sponge size and ventilation system into account. In short, DHS system is recommended to replace conventional wastewater treatment for nutrients removal in the developing countries.